A hydrogen‐oxidizing bacterium enriched from the open ocean resembling a symbiont. Issue 4 (25th May 2020) - Sass, Katharina; Güllert, Simon; Streit, Wolfgang R.; Perner, Mirjam
Summary: A new autotrophic hydrogen‐oxidizing Chromatiaceae bacterium, namely bacterium CTD079, was enriched from a water column sample at 1500 m water depth in the southern Pacific Ocean. Based on the phylogeny of 16S rRNA genes, it was closely related to a scaly snail endosymbiont (99.2% DNA sequence identity) whose host so far is only known to colonize hydrothermal vents along the Indian ridge. The average nucleotide identity between the genomes of CTD079 and the snail endosymbiont was 91%. The observed differences likely reflect adaptations to their specific habitats. For example, CTD079 encodes additional enzymes like the formate dehydrogenase increasing the organism's spectrum of energy generation pathways. Other additional physiological features of CTD079 included the increase of viral defence strategies, secretion systems and specific transporters for essential elements. These important genome characteristics suggest an adaptation to life in the open ocean.